THE LACK OF TECHNOLOGICAL EQUIPMENT IN UZBEKISTAN’S OUTSKIRTS SCHOOLS - Ahrorova Gulsanam Husan qizi; Kurbanova Feruza (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the challenges faced by secondary schools in the outskirts of Uzbekistan regarding their lack of technological equipment and infrastructure. Since the country’s independence, the gap between urban and rural schools in terms of access to modern educational resources has widened. Through a detailed analysis of existing literature, surveys, and interviews with educators and students, the study identifies key issues such as limited access to computers, poor internet connectivity, and insufficient teacher training. It also highlights the negative impact of these challenges on student performance and digital literacy. The article proposes practical solutions, including increased investment in technology, professional development for teachers, and improved internet access, aimed at bridging the digital divide and creating a more equitable educational environment. By addressing these issues, the study seeks to contribute to the development of better learning opportunities and educational facilities in the rural regions of Uzbekistan.